PENGEMBANGAN KOMIK FISIKA BERBASIS SAINTIFIK MATERI GELOMBANG BUNYI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI MAN 1 (MODEL) LUBUKLINGGAU - Anggun Ari Aditia Utami; Wahyu Arini; Tri Arini (LP4MK STKIP PGRI Lubuklinggau, 2023)
This development research aims to (1) determine the quality of science-based physics comics on sound wave material and (2) improve students' physics learning outcomes after participating in learning activities using scientific-based physics comics on sound wave material. This research is a development research using a 4D model. The subjects of this study included students of class XI MIPA 2 MAN 1 Lubuklinggau. Data collection techniques were carried out using validation sheets and learning achievement tests. Based on the results of validation by material experts of 0.95; media experts at 0.89; and linguists at 0.87. Thus scientific-based physics comics are appropriate for use in classroom learning activities. And the results of the analysis of increasing student learning outcomes through questions with pretest and posttest learning outcomes tests. Increased mastery of physics material after students use scientific-based physics comics developed after being analyzed with a Gain Score score of 0.79 is included in the very high category. Based on the research data obtained, it can be concluded that science-based physics comics on sound waves for class XI developed by researchers are declared valid and can improve student learning outcomes so that they can be used in learning activities.